3, 4-Ethylenedioxythiophene (EDOT) and 3, 4-ethylenedithiathiophene (EDTT) as terminal blocks for oligothiophene dyes for DSSCs. Issue 43 (26th October 2016) - Demeter, Dora; Melchiorre, Fabio; Biagini, Paolo; Jungsuttiwong, Siriporn; Po, Riccardo; Roncali, Jean
Graphical abstract: Highlights: Synthesis of metal-free sensitizers for dye-sensitized solar cells. Analysis of the effect of the structure of the terminal thiophenic ring. Replacement of EDOT by EDTT leads to a noticeable improvement in conversion efficiency. Abstract: Thiophene pentamers with a cyanoacrylic acid anchoring group at one end and 3, 4-ethylenedioxythiophene (EDOT) or 3, 4-ethylenedithiathiophene (EDTT) units at the other end have been synthesized. Preliminary evaluation in DSSCs with a iodide/triiodide liquid electrolyte shows that in spite of the very close electronic properties of the two dyes, replacing EDOT by EDTT leads to a noticeable improvement of conversion efficiency under simulated solar light.